ANALISIS MOTIVASI KONSUMEN DAN IMPULSIVE BUYING DALAM BERBELANJA ONLINE E-COMMERCE INDONESIA - Rahmawati, Yulia; Pristiyono, Pristiyono; Gulo, Nur’ainun (ITB AAS Indonesia Surakarta, 2024)
This research aims to determine the analysis of consumer motivation and impulsive buying in online shopping for Indonesian e-commerce. The total sample was 150 respondents, namely people from Kampung Rakyat District who shopped using the Shopee application. This research uses data processing assistance, namely smart pls version 4.0, by conducting outer model testing, inner capital testing and bootstrapping (hypothesis testing). In the outer model test, the test was carried out by looking at the outer loading, average variance extracted (AVE), cross loading reliability and Cronbach alpha values, all research results were said to be good, in the inner model test there were 2 equations produced by r square with the highest r square value found in the second equation, namely impulsive buying. In hypothesis testing, it was found that the research results of all research hypotheses were accepted with the results that the website quality variable had an effect on consumer motivation (2.723>1.96), advertising policy had an effect on consumer motivation (2.723>1.96), Consumer motivation influences impulsive buying (2.723>1.96), and smartphone penetration influences consumer motivation (2.723>1.96).